Inside Cover. Issue 8 (2nd August 2020) - Liberda, Danuta; Hermes, Michael; Koziol, Paulina; Stone, Nick; Wrobel, Tomasz P.
Abstract: Esophagus tissue classification models based on FT‐IR imaging data were successfully created (AUC>0.95). The conditions for translating a histopathological FT‐IR based model to a fast Quantum Cascade Laser (QCL) system microscope were investigated. Further details can be found in the article by Danuta Liberda, Michael Hermes, Paulina Koziol, Nick Stone and Tomasz P. Wrobel (e202000122 ). Abstract : Esophagus tissue classification models based on FT‐IR imaging data were successfully created (AUC>0.95). The conditions for translating a histopathological FT‐IR based model to a fast Quantum Cascade Laser (QCL) system microscope were investigated. Further details can be found in the article by Danuta Liberda, Michael Hermes, Paulina Koziol, Nick Stone and Tomasz P. Wrobel (e202000122 ).